Peningkatan Pemberdayaan Tenaga Promosi Kesehatan dengan Media Edukasi dan Promosi Kesehatan di Kota Depok - Nalawati, Rizki Elisa; Mera Kartika Delimayanti; Dewi Kurniawati; Mahesa Rama Triwijaya (Unit Publikasi Ilmiah, P3M, Politeknik Negeri Bali, 2024)
Increasing public health awareness is an important strategic issue to be handled by local governments, especially in the Depok City area. This strategic issue is handled directly by the Depok City Health Service. This is a result of the lack of public health awareness, which is a challenge in health promotion efforts in Depok City. Several technical obstacles were encountered in the field related to limited technical capabilities in using software to create educational and promotional media using technology. This technical ability can be overcome by providing counseling and technical assistance using a selection of simple, smartphone-based tools. This training involved 60 health promoters from community health centers and regional hospitals in Depok City. The pretest results, which illustrate the success of the community service process, stated that 47.2% of health promotion workers rarely received multimedia training, and 17.85% felt that there had never been any multimedia training. Positive responses were given by the participants, as shown by the results of the implementation of 2-dimensional and 3-dimensional multimedia